Alternative Glycerol Balance Strategies among Saccharomyces Species in Response to Winemaking Stress - Pérez-Torrado, Roberto; Oliveira, Bruno M.; Zemančíková, Jana; Sychrová, Hana; Querol, Amparo (Frontiers in Microbiology, 2016)
Production and balance of glycerol is essential for the survival of yeast cells in certain stressful conditions as hyperosmotic or cold shock that occur during industrial processes as winemaking. These stress responses are well known in S. cerevisiae, however, little is known in other phylogenetically close related Saccharomyces species associated with natural or fermentation environments such as S. uvarum, S. paradoxus or S. kudriavzevii. In this work we have investigated the expression of four genes (GPD1, GPD2, STL1 and FPS1) crucial in the glycerol pool balance in the four species with a biotechnological potential (S. cerevisiae; S. paradoxus; S. uvarum and S. kudriavzevii), and the ability of strains to grow under osmotic and cold stresses. The results show different pattern and level of expression among the different species, especially for STL1. We also studied the function of Stl1 glycerol symporter in the survival to osmotic changes and cell viability in winemaking environments. These experiments also revealed a different functionality of the glycerol transporters among the different species studied. All these data point to different strategies to handle glycerol accumulation in response to winemaking stresses as hyperosmotic or cold-hyperosmotic stress in the different species, with variable emphasis in the production, influx or efflux of glycerol.